Some problems of IT-infrastructure administration: current status and prospects - Ткачук, Микола В’ячеславович; Сокол, Владислав Євгенович (Eastern-European Journal of Enterprise Technologies, 2010)
The problems of creation and applications a new class of ACS were considered, namely, systems management of IT services of organizations, provides a comparative overview of some existing systems and diagram of a typical function was built.